Mucormycosis in a Severe Trauma Patient Treated with a Combination of Systemic Posaconazole and Topical Amphotericin B-Case Report - Keller, Filip; Antoni, Helena; Minarcikova, Petra; Hrdy, Ondrej; Gal, Roman (Antibiotics (Basel, Switzerland), 2023)
Mucormycosis is an opportunistic infection affecting mainly immunocompromised hosts. Infection in immunocompetent patients is rare, but may occur typically in trauma or burn victims. We report on a previously healthy young man suffering devastating trauma from an agricultural accident with the subsequent development of a multifocal mucormycosis. Diagnosis was achieved by cultures obtained from non-healing wounds, some of them even covered by a macroscopic mold formation. Specific treatment was initiated soon after the preliminary results indicated mucormycosis. Aggressive surgical therapy, with concomitant use of systemic posaconazole and topical amphotericin B in a combination treatment, led to the elimination of the fungal infection. The remaining deep tissue defects were consequently reconstructed by a muscle flap and skin graft autotransplantation with a good overall outcome, which would not have been possible without the complete remission of mucormycosis. This case study presents the successful use of a combination treatment with systemic posaconazole and topical amphotericin B and underlines the importance of timely and aggressive surgical therapy.
Keywords: posaconazole; amphotericin B; case report; severe trauma; mucormycosis